Reservoir Cannulas for Pediatric Oxygen Therapy: A Proof-of-Concept Study - Grace Wu; Alec Wollen; Robert M. DiBlasi; Stephen Himley; Eugene Saxon; Glenn Austin; Jaclyn Delarosa; Rasa Izadnegahdar; Amy Sarah Ginsburg; Darin Zehrung (Hindawi Limited, 2016)
Hypoxemia is a complication of pneumonia-the leading infectious cause of death in children worldwide. Treatment generally requires oxygen-enriched air, but access in low-resource settings is expensive and unreliable. We explored use of reservoir cannulas (RCs), which yield oxygen savings in adults but have not been examined in children. Toddler, small child, and adolescent breathing profiles were simulated with artificial lung and airway models. An oxygen concentrator provided flow rates of 0 to 5 L/min via a standard nasal cannula (NC) or RC, and delivered oxygen fraction (FdO2) was measured. The oxygen savings ratio (SR) and absolute flow savings (AFS) were calculated, comparing NC and RC. We demonstrated proof-of-concept that pendant RCs could conserve oxygen during pediatric therapy. SR mean and standard deviation were 1.1±0.2 to 1.4±0.4, 1.1±0.1 to 1.7±0.3, and 1.3±0.1 to 2.4±0.3 for toddler, small child, and adolescent models, respectively. Maximum AFS observed were 0.3±0.3, 0.2±0.1, and 1.4±0.3 L/min for the same models. RCs have the potential to reduce oxygen consumption during treatment of hypoxemia in children; however, further evaluation of products is needed, followed by clinical analysis in patients.